Analysis of the Utilization of Social Media Monitoring @Roseallday.Co Instagram to Prevent Cancel Culture Crisis - Prihardana, Marsha Aliffia; Lestari, Martha Tri (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The cancel culture phenomenon has become a very significant part in the Indonesian society. With the information technology advancement, various of marketing activities nor a reputation rejuvenation are mostly utilizing the social media. One of the activities of the public relations team is social media monitoring especially on Instagram. This paper will do research on one of Indonesian beauty company, Rose All Day, which get cancelled by the online society due to its controversial issue which caused the company being cancelled. This research uses a descriptive method with qualitative approach with Naives Bayes Classifier mechanism to help analyze the sentiment. The results of the research and discussion that has been carried out by the author, a conclusion was obtained that the sentiment analysis reveals that 53.53% of the comments are positive, 25.84% are neutral, and 20.63% are negative. Social Media Listening is essential before Social Media Monitoring, as it helps the company track communication efforts on platforms like Instagram to prevent further cancel culture issues.